Pengaruh Proporsi Dewan Komisaris Perempuan terhadap Kinerja Keuangan Perusahaan: Peran Mediasi Tanggung Jawab Lingkungan Perusahaan - Nadilla Nur Azizah; Rita Wijayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of the proportion of female commissioners on the company's financial performance using the moderating variable of corporate environmental responsibility. This study uses a quantitative research type. The population of this study is companies that are classified as environmentally sensitive industries in Indonesia using a sample of 163 companies. The sample selection used a purposive sampling method. The results of this study indicate that WoB has a positive effect on CERE, CERE has a positive effect on CFP, and CERE mediates WoB and CFP. This study helps companies develop more effective and sustainable development strategies to produce better corporate financial performance, in addition, this study can prove that the role of women in the board of commissioners is very helpful in increasing corporate environmental responsibility in order to create better corporate financial performance.